Children's conceptualization of law enforcement on television and in real life - Low, Jason (Legal and criminological psychology, 2001)
Purpose. Television police dramas provide viewers with an inaccurate representation of police work, overemphasizing sensational and dramatic activities while underemphasizing routine duties. This raises the critical issue of whether such misrepresentations are reflected in children's perceptions of law-enforcement activities in real life. Method. A total of 96 children (Grades 1, 3, 5 and 7) were asked to make estimates regarding how often various law-enforcement activities occurred on TV police shows and in real life. The relative contributions of age, perceived usefulness of police shows and real life models for learning about law enforcement and viewing frequency of police shows in predicting children's estimations at law enforcement were assessed. Results. Activities overrepresented on TV were perceived by children to be relatively frequent in real life police work. Activities underepresented on TV shows were perceived by children to be relatively infrequent in real life. The more children (especially first graders) reported watching TV police shows, and the more they perceived them contributing to their knowledge about police work, the more inaccurate was their perception of law enforcement in real life. Perceived informativeness of real life models did not predict children's perceptions of law enforcement in real life.